INFLUENCE OF COMPETITIVE ENVIRONMENT AND INSTITUTIONAL FACTORS ON SMALL BUSINESS (Marketing Journal, 2026)
Small business plays a key role in the economy of Uzbekistan, accounting for more than half of the country’s gross domestic product and creating significant employment opportunities. This article examines how the competitive environment and institutional f actors influence the development of small entrepreneurship in the context of Uzbekistan’s transition economy. The study employs methods of statistical № 1 -SON YANVA R, 202 6-YIL 389 data analysis, review of the regulatory and legal framework, and an overview of relevant contemporary literature. The results indicate that a healthy competitive environment stimulates innovation and growth among small enterprises, while institutional barr iers such as complex regulations and bureaucracy can significantly constrain their development. The study concludes that consistent economic reforms and strengthened institutional support can enhance the competitiveness of small businesses and increase the ir contribution to sustainable economic growth.
Keywords: small business; competitive environment; institutional factors; entrepreneurship; Uzbekistan; economic development